Recommendation for treatment of hepatitis C virus infection - Kaymakoğlu, Sabahattin; Köksal, İftihar and Tabak, Fehmi and Akarca, Ulus S. and Akbulut, Ayhan and Akyüz, Filiz and Bodur, Hürrem and Çağatay, Atahan and Dinçer, Dinç and Esen, Şaban and et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Kaymakoğlu S, Köksal İ, Idilman R; Viral Hepatitis Guidelines Study Group. Recommendation for treatment of hepatitis C virus infection. Turk J Gastroenterol 2017; 28(Suppl 2); SX-SX.